Fairway Traffic Capacity in Indonesia. (2017) - Kadarsa, Edi; Lubis, Harun al-Rasyid S.; Sjafruddin, Ade; Frazila, Russ Bona
Abstract: Problems of congestion and road damage due to traffic density and excessive vehicle loads can be solved by shifting the traffic load of the highway to river transport. For regional areas in Indonesia, which are traversed by rivers with water levels and width navigable by various types of vessels, river transport can be the main alternative transportation of goods other than highways. South Sumatra is one of the provinces in Indonesia which has a network of rivers that can be traversed by large cargo vessels. Musi River with its tributaries network is the main fairway in South Sumatra where water levels of the river are affected by the environment, especially tides, seasons and sedimentations. This environmental influences have led to vessels being unable to sail safely and smoothly all the time. Therefore, it is deemed necessary to determine the fairway capacity as a riverway performance indicator that takes into account environmental influences, especially tides. Various research on capacity of inland waterways previously conducted have not specifically considered the effect of tides.